2008
DOI: 10.1086/529382
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity of Human Leukocyte Antigen–B*5701 as a Marker for Immunologically Confirmed Abacavir Hypersensitivity in White and Black Patients

Abstract: Although IC ABC HSRs are uncommon in black persons, the 100% sensitivity of HLA-B*5701 as a marker for IC ABC HSRs in both US white and black patients suggests similar implications of the association between HLA-B*5701 positivity and risk of ABC HSRs in both races.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
236
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(260 citation statements)
references
References 23 publications
(40 reference statements)
9
236
2
4
Order By: Relevance
“…It was a casecontrol study that enrolled both white and black patients in the USA. 40 This study showed that 100% of both white and black patch test-positive patients carried HLA-B*5701, suggesting a predictive value of HLA-B*5701 for abacavir-induced hypersensitivity across ethnicities. This study demonstrated the clinical utility of testing for HLA-B*5701 prior to prescription of abacavir.…”
Section: Abacavirmentioning
confidence: 65%
“…It was a casecontrol study that enrolled both white and black patients in the USA. 40 This study showed that 100% of both white and black patch test-positive patients carried HLA-B*5701, suggesting a predictive value of HLA-B*5701 for abacavir-induced hypersensitivity across ethnicities. This study demonstrated the clinical utility of testing for HLA-B*5701 prior to prescription of abacavir.…”
Section: Abacavirmentioning
confidence: 65%
“…83 Thus, HLA-B*5701 screening has been shown to reduce the risk of hypersensitivity reaction to abacavir, with a reported negative predictive value for immunologically confirmed hypersensitivity reaction of 100% in white and black individuals. 70,84 The positive predictive value of a positive HLA-B*5701 result is much lower, with 55% of those carrying the allele able to tolerate abacavir; however, it is not recommended to use abacavir in those at risk. 70 Lactic Acidosis with Hepatic Steatosis.…”
Section: Acute Eventsmentioning
confidence: 99%
“…HLA-B*5701 screening is an effective way to prevent exposure to abacavir in susceptible subjects. 70,84 A close follow-up and selection of patients with lower CD4 counts in antiretroviral-naïve patients can minimize the risk of nevirapine-related idiosyncratic reactions with liver involvement. It is unclear if this also applies to treatment-experienced subjects, although it seems prudent to take the same precaution when there is not complete viral suppression.…”
Section: Prevention and Management Of Haart Liver Toxicitymentioning
confidence: 99%
“…The HLA region is the most polymorphic locus in the genome, which further complicates studies. Nevertheless, this association has been confirmed in different ethnicities despite of the fact that the prevalence of the HLA-B*57:01 across different ethnic groups is heterogeneous (Caucasians 4%, Asians 2%, Hispanics 1% and Blacks 0.5%) [75][76][77][78]. One of the most important studies supporting the clinical usefulness of the screening of the HLA-B*57:01 was the one published by Mallal et al [75] in 2008 in which a large number of patients were enrolled.…”
Section: Pharmacogenetics Of Abacavirmentioning
confidence: 97%
“…One of the most important studies supporting the clinical usefulness of the screening of the HLA-B*57:01 was the one published by Mallal et al [75] in 2008 in which a large number of patients were enrolled. Prospective studies as well as cost-effectiveness studies of HLA-B*51:01 testing have force its incorporation in the HIV treatment guidelines before prescribing ABC [78][79][80][81]. In fact, the HLA-B*51:01 testing has been the first pharmacogenetic test used in the clinical practice to the management of HIV infection.…”
Section: Pharmacogenetics Of Abacavirmentioning
confidence: 99%